Nonparametric statistical analysis for multiple comparison of machine learning regression algorithms - Trawiński, Bogdan; Smętek, Magdalena; Telec, Zbigniew; Lasota, Tadeusz (Zielona Góra: Uniwersytet Zielonogórski)
In the paper we present some guidelines for the application of nonparametric statistical tests and post-hoc procedures devised to perform multiple comparisons of machine learning algorithms. We emphasize that it is necessary to distinguish between pairwise and multiple comparison tests.
Keywords: machine learning; nonparametric statistical tests; statistical regression; neural networks; multiple comparison tests